The N-terminus of the RNA polymerase from infectious pancreatic necrosis virus is the determinant of genome attachment. - Stephen C Graham; L Peter Sarin; Mohammad W Bahar; Reg A Myers; David I Stuart; Dennis H Bamford; Jonathan M Grimes (PLoS Pathogens)
The RNA-dependent RNA polymerase VP1 of infectious pancreatic necrosis virus (IPNV) is a single polypeptide responsible for both viral RNA transcription and genome replication. Sequence analysis identifies IPNV VP1 as having an unusual active site topology. We have purified, crystallized and solved the structure of IPNV VP1 to 2.3 Å resolution in its apo form and at 2.2 Å resolution bound to the catalytically-activating metal magnesium. We find that recombinantly-expressed VP1 is highly active for RNA transcription and replication, yielding both free and polymerase-attached RNA products. IPNV VP1 also possesses terminal (deoxy)nucleotide transferase, RNA-dependent DNA polymerase (reverse transcriptase) and template-independent self-guanylylation activity. The N-terminus of VP1 interacts with the active-site cleft and we show that the N-terminal serine residue is required for formation of covalent RNA:polymerase complexes, providing a mechanism for the genesis of viral genome:polymerase complexes observed in vivo.